2013
DOI: 10.1021/ol402913m
|View full text |Cite
|
Sign up to set email alerts
|

Cephalosporolide B Serving as a Versatile Synthetic Precursor: Asymmetric Biomimetic Total Syntheses of Cephalosporolides C, E, F, G, and (4-OMe-)G

Abstract: Cephalosporolide B (Ces-B) was efficiently synthesized and exploited for the first time as a versatile biomimetic synthetic precursor for the chemical syntheses of not only cephalosporolides C, G, and (4-OMe-) G via a challenging diastereoselective oxa-Michael addition but also the structurally unprecedented cephalosporolides E and F via a novel biomimetic ring-contraction rearrangement. These findings provide the first direct chemical evidence that Ces-B may be the true biosynthetic precursor of cephalosporol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…All syntheses involved Yamaguchi marolactonization as a key step to construct the 8-membered lactone. The synthesis reported by Tong et al [34] is based on an oxidative ring expansion of b-hydroxyethers [35] as a key step to construct the 10-membered lactone. The rhododendrol 55 was protected as TBS ether 56 and then subjected to phenol dearomatization, desilylation, and subsequent oxa-Michael cyclization to provide bicyclic ether 57 as a single diastereomer (Scheme 10).…”
Section: H) Srinivasareddy's Synthesis Of (à)-Cephalosporolide D (2015)mentioning
confidence: 99%
See 2 more Smart Citations
“…All syntheses involved Yamaguchi marolactonization as a key step to construct the 8-membered lactone. The synthesis reported by Tong et al [34] is based on an oxidative ring expansion of b-hydroxyethers [35] as a key step to construct the 10-membered lactone. The rhododendrol 55 was protected as TBS ether 56 and then subjected to phenol dearomatization, desilylation, and subsequent oxa-Michael cyclization to provide bicyclic ether 57 as a single diastereomer (Scheme 10).…”
Section: H) Srinivasareddy's Synthesis Of (à)-Cephalosporolide D (2015)mentioning
confidence: 99%
“…A similar chemistry was employed by Tong as described earlier (Scheme 10). [34] Finally, deprotection of the TBS group followed by regioselective reductive opening of the epoxide afforded cephalosporolide G 6 with the (3S,4R,9R) absolute configuration at the stereogenic centers.…”
Section: C) Carreno's Synthesis Of Cephalosporolide G and C3-epicephamentioning
confidence: 99%
See 1 more Smart Citation
“…[1] The relative stereochemistry within the tricyclic core of the ascospiroketals was established from analysis of NOESY experiments and confirmed that these compounds are anomeric spiroacetals. Structurally, these compounds represent the most complex members of a small family of tricyclic 5,5-spiroacetals [2] that includes the cephalosporolides, [3] penisporolides, [4] and opaliferin, [5] for which several potentially useful biological activities have been ascribed. Thus, the relative stereochemistry of the three remote stereocenters remained undefined.…”
Section: In2007kçnigreportedtheisolationofascospiroketals a (1)mentioning
confidence: 99%
“…Pyridinium chlorochroamte (PCC) is a well known oxidizing reagent. Although it is mostly used in the oxidation of primary and secondary alcohols to aldehydes and ketones, respectively, it has also been employed in a number of other processes [5], and recently, we [6][7][8][9] and others [10][11][12][13][14] have disclosed its ability to catalyze new synthetically useful reactions. We were now interested in testing some oxidative methods previously developed in our laboratories [8, [15][16][17] on a number of structurally diverse molecular frameworks in order to access a selection of variously functionalized substances for structure-activity relationship studies [18].…”
Section: Introductionmentioning
confidence: 99%